RENO PROTECTIVE ROLE OF N ACETYL CYSTEINE AND AQUEOUS EXTRACT OF BERBERIS LYCIUM ROYALE ROOT BARK ON RATS - Ijaz, Nimra; Akbar Waheed; Mehwish Tayyab; Sidra Mumal; Rabia Iftikhar; Alia Rehman; Esha Akram (Journal of Ayub Medical College Abbottabad, 2021)
Background: N acetyl cysteine and Berberis lycium Royale root bark have been used to treat kidney diseases. Objectives of the study were to evaluate the individual and combined effect of N acetyl cysteine and aqueous extract of Berberis lycium Royale root bark in Gentamicin induced nephrotoxicity in rats. This randomized control trial conducted at Islamic International Medical College, Rawalpindi in collaboration with NIH, Islamabad in 1 month from Sep to Oct 2020. Methods: Fifty Wister albino rats of 10-12 weeks old were divided into five groups with 10 in each group. Group 1 was normal control given food and water only and remaining 40 were in treatment groups. Nephrotoxicity was induced by intraperitoneal injection of Gentamicin (80mg/kg) for 6 days in group 2, 3, 4 and 5. After induction of nephrotoxicity, Group 3 was administered N acetyl cysteine 140mg/kg per oral, Group 4 was given aqueous extract of Berberis lycium Royale root bark 400 mg/kg per oral and Group 5 was given both N acetyl cysteine 140mg/kg per oral and aqueous extract of Berberis lycium Royale root bark 400 mg/kg per oral for 21 days. Serum uric acid was measured in all groups after 30 days to observe the reversal of renal injury. Results: The results of this study indicate that Group 3, Group 4 and Group 5 showed a decrease in serum uric acid level as compared to Disease Control Group (Group 2). However, Group 5 significantly reduced uric acid (p-0.05). Conclusion: Combined effect of N acetyl cysteine and aqueous extract of Berberis lycium Royale root bark showed improvement in uric acid level in Gentamicin induced nephrotoxicity in rats.